Use of Traditional and Complementary Medicine as Self-Care Strategies in Community Health Centers: Cross-Sectional Study in Urban Pearl River Delta Region of China. Issue 23 (June 2016) - Chung, Vincent C.H.; Wong, Samuel Y.S.; Wang, Harry H.X.; Wong, Martin C.S.; Wei, Xiaolin; Wang, Jiaji; Liu, Siya; Ho, Robin S.T.; Yu, Ellen L.M.; Griffiths, Sian M.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: In China, Community Health Centers (CHCs) are major providers of primary care services, but their potential in empowering patients' self-management capacity has not been assessed. This study aims to describe self-care practice patterns amongst CHC attendees in urban China. In this cross-sectional quantitative study, 3360 CHC patients from 6 cities within the Pearl Delta Region were sampled using multistage cluster sampling. Thirty-seven per cent had used with over-the-counter Chinese herbal medicines (OTC CHMs) in the past year and majority of respondents found OTC CHMs effective. OTC CHMs were more popular amongst those who needed to pay out of pocket for CHC services. Less than 10% used vitamins and minerals, and those with a lower socioeconomic background have a higher propensity to consume. Although doubts on their usefulness are expressed, their use by the vulnerable population may reflect barriers to access to conventional health care, cultural affinity, or a defense against negative consequences of illnesses. About 25% performed physical exercise, but the prevalence is lower amongst women and older people. Taiji seems to be an alternative for these populations with promising effectiveness, but overall only 6% of CHC attendees participated. These results suggest that CHCs should start initiatives in fostering appropriate use of OTC CHM, vitamins, and minerals. Engaging community pharmacists in guiding safe and effective use of OTC CHM amongst the uninsured is essential given their low accessibility to CHC services. Prescription of Taiji instead of physical exercises to women and older people could be more culturally appropriate, and the possibility of including this as part of the CHC services worth further exploration.